EKSISTENSI GURU (MURSYID) DALAM PENDIDIKAN SPIRITUAL PERSPEKTIF ABÛ HÂMID AL-GHAZÂLÎ (1058M-1111M) - Akhmansyah, Muhammad (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2015)
Al-Ghazali was one of the most influential Muslim thinkers. A jurist, logician, theologian, and philosopher, thinker on education in Islamic history and he was honoured in the history of Islam with title of Hujjat al-Islâm. He developed  a  theory of  education  rooted in  his philosophy and  aiming at improving the objectives and principles of education.  According to Ghazali, knowledge can bring us closer to God as well as enhance worldly respect and position. Ghazali based his aims of education on Islamic ideology. According to him, every student should have a shaykh or a mursyid (spiritual guide or teacher) to instruct him and cleanse him of bad manners through the process of tarbiyah, and replace them with good character. The follower of the path requires a mursyid to improve his character and guide him   upon the path towards Allah (SWT) the Exalted. The article shall axplain further Ghazali‟s thought specially in existence of mursyid in spiritual education.